Understanding Children’s Drawings as Sociomaterial Assemblages of Voice during Pandemic Times - Anne Burke (Language and Literacy: A Canadian Educational e-journal, 2023)
During the COVID-19 pandemic, schools transitioned to online learning. Utilizing sociomaterial assemblages and visual methods alongside interviews to prompt children’s voices, we collected drawings from primary students at two Eastern Canadian schools to achieve a multimodal understanding of children’s online learning experiences. Younger children’s drawings reflected the issues with technology and lack of socialization, while older children’s depicted their enjoyment with online learning with the agency afforded by learning from home. We found that pedagogical creativity and innovation were essential to successful online learning. This research demonstrates the efficacy of a sociomaterial perspective on children’s drawings for eliciting children’s agentic voices.